Marvell's Maps: Reading Empire through Microcosm at Nun Appleton. - Normandin, Daniel (Early Modern Literary Studies, 2020)
The article informs that Andrew Marvell peruses Thomas Fairfax's library at Nun Appleton with books including Thomas Gage's "The English-American his Travail by Sea and Land", and Edward Norgate's "Miniatura." Topics include virtue of political withdrawal without unduly slighting the virtue of expansive political and military activity; and national expansion is transmuted into the techniques of poetic figuration.